Discovery and Characterization of an Endo-1,3-Fucanase From Marine Bacterium Wenyingzhuangia fucanilytica: A Novel Glycoside Hydrolase Family - Shen, Jingjing; Chang, Yaoguang; Zhang, Yuying; Mei, Xuanwei; Xue, Changhu (Frontiers in Microbiology, 2020)
Sulfated fucans are important marine polysaccharides widely distributed in brown algae and echinoderms, which gained increasing research interest for their various biological and biomedical activities. Fucanases could be served as tools in the bioconversion and structural investigation of sulfated fucans. A few gene-defined endo-1,4-fucanases have been characterized, while the sequence of endo-1,3-fucanase remain unstudied. Here, an endo-1,3-fucanase gene funA was screened from the genome of marine bacterium Wenyingzhuangia fucanilytica CZ1127T using transcriptomics. None of the previously reported glycosidic hydrolase domains were predicted in the enzyme FunA, which hydrolyzed sulfated fucans in a random endo-acting manner. Ultrahigh performance size exclusion chromatography-mass spectrometryand nuclear magnetic resonance analyses revealed that FunA specifically cleaves α-1,3glycosidic linkage between 2-O-sulfated and nonsulfated fucose residues. FunA exhibited transglycosylating activity with glycerin, methanol, and L-fucose as acceptors. D206 and E264 were critical for the functioning of FunA as identified by the site-directed mutagenesis. Another five homologues of FunA were confirmed to possess endo-1,3-fucanse activities. This is the first report on the sequence of endo-1,3-fucanase. The novelty of FunA and its homologues in sequences and activity shed light on a novel glycoside hydrolase family.